Imaging of Vascular Injuries of the Extremities - Nicola, Refky; Kawakyu-O'Connor, Don; Scalgione, Mariano (Seminars in Musculoskeletal Radiology, 2017)
Multidetector computed tomography angiography (MDCTA) of the upper and lower extremities is the standard of care in the assessment of trauma patients with vascular trauma of the upper and lower extremities. A MDCTA of the extremities is typically integrated into multiphasic whole-body computed tomography trauma protocols in patients with suspected vascular injury. MDCTA has replaced catheter-directed digital subtraction angiography (DSA) as the modality of choice for the initial detection and characterization of vascular injuries because it is readily available, noninvasive, and faster than DSA. Understanding the imaging findings and pitfalls of upper and lower extremity MDCTA is essential in the diagnosis of vascular injuries such as active hemorrhage, vasospasm and stenosis, hematoma, occlusion and thrombosis, posttraumatic arteriovenous fistula, pseudoaneurysm, and patterns of intimal injury including dissection. We discuss the diagnosis and characterization of vascular injuries of the upper and lower extremities using MDCTA including derived multiplanar reconstructions, maximum intensity projection, and three-dimensional volume rendering techniques.
Keywords: MDCT angiography; upper extremity trauma; lower extremity trauma; vascular injury; computed tomography; 3DCT; MIP; MPR; VR